Walking as Space Making by Humayun Ahmed’s Himu - Mondol, Md Shamim; Islam, Md Samiul (Green University Review of Social Sciences, 2022)
A city space beyond its structural execution by the planners and administrators is consistently acted out by those who perform daily practices in those spaces. A walker as a regular practitioner appropriates the space, invents and inscribes stories there causing transgression in the imposition by the dominant structures and cultures. Humayun Ahmed, a well-known writer in Bangladeshi literature, has created the popular juvenile fictional character Himu, as a walker in the streets of Dhaka with no confinement encountering others and rewriting stories and histories unacknowledged in dominant discourses. This paper studies Himu, the quintessential walker, as a space-producing agency that problematizes many of the taken-for-granted practices in the streets. He routes through the streets of Dhaka and orchestrates before us multiple stories. With insights from de Certeau’s “Walking in the City” from The Practice of Everyday Life, this paper focuses on walker Himu and shows his space-creating activities as digressive as well as transgressive in creative ways to dismantle the dominant culture which are commonly acted out by the common practitioner in the streets. Green University Review of Social Sciences Dec 2021; 7(1-2): 201-207